An in vitro study on comparative adherence of oral Candida albicans and non–albicans Candida to human buccal epithelial cells and its antifungal susceptibility pattern - P. A., Asina; Kumar K. S., Harish; Kuruvilla, Jacob; Das, Divya; S., Innu; Jayamohan, Rani S.; Mathews, Roopa (International Journal Of Community Medicine And Public Health, 2023)
Background: Candida spp. are intra-oral commensals in 40-60% of human subjects and the precise factors involved in the development of Candidiasis are still not clear. The adherence of Candida to epithelial cells is one of the main pathogenic characteristics of the genus. Studies have shown that there are variations in the adherence capabilities of different Candida spp., which may explain why some species colonize mucosal surfaces more frequently than others. The aim of this study was to estimate the adherence properties of Candida spp. to buccal epithelial cells and to determine the antifungal susceptibility. Methods: 87 isolates of Candida spp. from known non-diabetic patients with oral Candidiasis were collected from diagnostic microbiology laboratories in central Kerala. The method of Kimura and Pearsall et al was followed with minor modifications to test the adherence. Results: All the three species exhibited adherence with varying capacity. C. albicans was significantly more adherent to buccal epithelial cells than C. tropicalis and C. krusei. Resistance was not observed among the isolates against fluconazole, voriconazole and clotrimazole. Conclusions: In conclusion Candida spp. isolated from oral candidiasis patients exhibited a higher adherence capacity to normal human buccal epithelial cells considered an essential virulence property. As anticipated C. albicans displayed higher virulence activity than non-Candida albicans species.